Identification of neuromuscular targets for restoration of walking ability after stroke: Precursor to precision rehabilitation. (23rd November 2019) - Hancock, Nicola J.; Shepstone, Lee; Rowe, Philip; Pomeroy, Valerie M.
Abstract: Objectives: Restoration of walking is a priority for stroke survivors and key target for physical therapies. Upright pedalling (UP) can provide functional walking‐like activity using a variety of muscle synergies; it is unclear which synergies might be most useful for recovery of walking. Objectives here were as follows: to examine whether neuromuscular measures derived during UP might identify targets for walking rehabilitation after stroke and to determine test–retest repeatability and concurrent validity of the measures. Design: This was a prospective correlational study. Setting: The study was carried out in a movement science laboratory. Participants: The participants were 18 adults with stroke (StrS) and 10 healthy older adults (HOA). Intervention/measurement: StrS and HOA took part in two identical measurement sessions. During UP, surface electromyography and kinematic data were recorded and then processed to derive three measures: reciprocal activity of quadriceps and hamstrings; percentage muscle activity "on" according to crank angle; and smoothness of movement. Results: HOA and StrS demonstrated differences in reciprocal muscle activity ( p = .044) and quadriceps activity according to crank angle ( p = .034) but pedalled similarly smoothly ( p = .367). For muscle activation according to crank angle in StrS, intraclass correlation coefficients (95% confidence interval) showing acceptable repeatability were 0.46 [0.32, 0.58] affected quadriceps; 0.43 [0.28, 0.56] affected hamstrings; and 0.67 [0.56, 0.75] unaffected quadriceps. Conclusion: Muscle activation according to crank angle is a promising measure of lower limb impairment during functional activity after stroke; subsequent investigation should determine magnitude of variance between testing sessions. Reciprocal activity of quadriceps and hamstrings muscles and quadriceps activity according to crank angle are both potential targets for physical therapies to improve motor recovery. Further investigations are warranted.